The effects of Nirvana fitness and functional training on the body appreciation of young women: non-randomized controlled trial - Jankauskiene, Rasa; Balciuniene, Vaiva; Rutkauskaite, Renata; Pajaujiene, Simona; Baceviciene, Migle (Frontiers in Psychology, 2024)
Exercise is an important intervention used to improve body image. The present non-randomized controlled trial aimed to examine the effects of Nirvana Fitness (NF) and functional training (FT) on body appreciation and its correlates in young women. Methods: Twentytwo students participated in FT, 21 in NF, and 47 in the control (CN) group. The mean age of the study participants was 22.79 ± 6.14 years. The FT and NF groups participated in sessions 2 days per week for 8 weeks, and the CN group did not participate in any sessions. All the participants were evaluated at pre-and post-intervention, filling in the Body Appreciation Scale 2 (BAS-2), Mind-Body Connection from the Physical Activity Body Experiences Questionnaire (PABEQ), Body Surveillance from the Objectified Body Consciousness Scale (OBCS), the Functionality Appreciation Scale (FAS), intrinsic exercise motivation from Behavioral Regulation in Exercise Questionnaire 2 (BREQ-2), and perceived physical fitness. Results: Significant improvements were found in terms of all outcome measures in the FT group, and improvements of body and mind connection and body surveillance in the NF group, while no improvements were observed in the CN group. FT's effect on body appreciation appeared to operate through the improvement of the mind-body connection in the FT and NF groups and via decreased body surveillance in the FT group. Conclusion: These findings support the developmental theory of embodiment and provide initial evidence that professionally delivered FT and NF might be used as effective strategies for the promotion of positive body image in young women.